New antibacterial agents: patent applications published in 2011. (January 2014) - Keating, Thomas A; Lister, Troy; Verheijen, Jeroen C
This article reviews 101 patent applications published in 2011 that disclosed small-molecule antibacterials and reported bacterial growth inhibition, in which the compounds were not similarly disclosed to be toxic to fungal or mammalian cells. The patent applications were analyzed according to their biological target and/or antibacterial class. Protein synthesis inhibitors included ligands of the 50S ribosome subunit (oxazolidinones, macrolides/ketolides and pleuromutilins), the 30S ribosome subunit (aminoglycosides and tetracyclines) and nonribosomal targets. DNA synthesis inhibitors included ligands of topoisomerase type II and type IV. Inhibitors directed at the bacterial cell envelope included those that act on cell envelope synthesis (LpxC inhibitors, penicillin-binding protein inhibitors and glycopeptides) as well as membrane disruptors (lantibiotics). Other antibacterial targets included cell division (FtsZ and WalR) and fatty acid biosynthesis (FabH/I). Compounds for which the targets are unknown or undisclosed are also covered, as are compounds aimed at overcoming resistance mechanisms (efflux inhibitors, β-lactamase inhibitors).